Developing a Dinan Exercise Therapy Model for Low Back Pain - Nanda, Fitri Agung; Mitsalina, Dinan; Rahmatullah, Muhammad Imam; Ali, Masnur; Wahyuti, Sri Ayu; Novriansyah, Novriansyah (Jurnal MensSana, 2023)
This study aims to produce a model of exercise therapy for low back pain, which is expected to be used by the community to restore low back pain. This study went through eight stages by adapting the research and development of Sugiyono model as follows: (1) information gathering in the field, (2) analysis of collected information, (3) initial product development, (4) expert validation and revision, (5) small scale and revised field trials, (6) large scale and revised field trials, (7) effectiveness testing, and (8) making final products. The small scale trials were conducted on six people and a large scale trial was conducted on 12 people using a minimum sample size formula at the Therapy Clinic of Injury at Yogyakarta State University Plaza. The instruments used to collect the data were expert validation sheets, questionnaire, Visual Analog Scale and midline to measure lumbar range of motion/lumbar flexibility. The results of the study are in the form of an exercise therapy model for low back pain consisting of 20 exercises therapy, 12 flexibility exercises and 8 muscle strengthening exercises, the flexibility exercises done in 4 sets, each held for 6 to15 seconds, and the type of muscle strengthening exercise in each movement being a combination of isometric and isotonic with repetitions of 6-12 repetitions, each end of the movement being held in 6 to10 seconds, for 3 sets, recovery between sets of 30 seconds to two minutes. Total duration about 20 to 30 minutes, frequency is 5x a week. The exercise therapy model can reduce pain levels by 37.357%, improve functional disability by decreasing the functional disability index by 28.684%, and increase lumbar flexibility with an average increase of 12.126%